Treatment of Blood Blister Aneurysms of the Internal Carotid Artery With Pipeline-Assisted Coil Embolization: A Single-Center Experience - Liu, Peng; Liu, Lunxin; Zhang, Changwei; Lin, Sen; Wang, Ting; Xie, Xiaodong; Zhou, Liangxue; Wang, Chaohua (Frontiers in Neurology, 2022)
Background: Blood blister aneurysm (BBA) is a complex and rare aneurysm that presents significant treatment challenges. The application of Pipeline embolization device (PED)-assisted coiling in the treatment of ruptured BBA remains controversial. This study aimed to report on our experience and assess the safety and efficacy of this strategy. Methods: Between February 2019 and February 2021, 12 patients with ruptured BBAs underwent PED-assisted coil embolization. We collected detailed data about each patient, including demographic information, aneurysmal data, technical details, antiplatelet strategy, operation-related complications, and follow-up outcomes. Results: A total of 12 BBA patients were treated with single PED-assisted coil embolization. One patient experienced intraoperative rupture that was controlled by rapid coiling without clinical consequences. All the patients demonstrated complete occlusion on postoperative angiography. A total of three patients had postoperative complications: left hemiparesis, Broca’s aphasia and right hemiplegia due to vasospasm, and transient hemiparesis. Follow-up angiography revealed that all BBAs were completely occluded, except one with neck residue. All patients had favorable outcomes at discharge and the most recent clinical follow-up (mRS score ≤ 2). Conclusion: Endovascular treatment of BBAs of the internal carotid artery using PED-assisted coil embolization is a safe and effective strategy. This has contributed to the understanding of BBA therapy and provides a potentially optimal treatment option for this intractable lesion.